Learning Environment, Mathematics Anxiety and Sex Differences - Taylor, B.; Fraser, Barry (James Nicholas Publishers, 2012)
Possible connections between, and sex differences in, mathematics anxiety and learning environment perceptions were investigated using quantitative and qualitative methods with 745 high school students in 34 different mathematics classrooms in four high schools in Southern California. The What Is Happening In this Class? (WIHIC) learning environment instrument, an updated Revised Mathematics Anxiety Rating Scale (RMARS) and student interview quotations analyses were used. Mathematics anxiety appears to have two factorially-distinct dimensions for which there were different patterns of sex differences and of associations with learning environment scales. Statistically significant sex differences were found for learning environment scales, especially in Task Orientation and Cooperation, but not mathematics anxiety. Associations between learning environment and anxiety emerged for Learning Mathematics Anxiety but not for Mathematics Evaluation Anxiety. Inductive analysis of student interview comments identified lower-order emergent themes that were built into higher-order themes that supported many of the quantitative findings.